The Responsiveness, Content Validity, and Convergent Validity of the Measure Yourself Concerns and Wellbeing (MYCaW) Patient-Reported Outcome Measure. (January 2015) - Jolliffe, Rachel; Seers, Helen; Jackson, Sarah; Caro, Elena; Weeks, Laura; Polley, Marie J.
Objective . Measure Yourself Concerns and Wellbeing (MYCaW) is a patient-centered questionnaire that allows cancer patients to identify and quantify the severity of their "concerns" and "wellbeing, " as opposed to using a predetermined list. MYCaW administration is brief and aids in prioritizing treatment approaches. Our goal was to assess the convergent validity and responsiveness of MYCaW scores over time, the generalizability of the existing qualitative coding framework in different complementary and integrative oncology settings and content validity. Methods . Baseline and 6-week follow-up data (n = 82) from MYCaW and FACIT-SpEx questionnaires were collected for a service evaluation of the Living Well with the Impact of Cancer course at Penny Brohn Cance Care. MYCaW convergent validity was determined using Spearman's rank correlation test, and responsiveness indices assessed score changes over time. The existing qualitative coding framework was reviewed using a new data set (n = 158) and coverage of concern categories compared with items of existing outcome measures. Results . Good correlation between MYCaW and FACIT-SpEx score changes were achieved ( r = −0.57, P ≥ .01). MYCaW Profile and Concern scores were highly responsive to change: standardized response mean = 1.02 and 1.08; effect size = 1.26 and 1.22. MYCaW change scores showed the anticipated gradient of change according to clinically relevant degrees of change. Categories, including "spirituality, " "weight change, " and "practical concerns" were added to the coding framework to improve generalizability. Conclusions . MYCaW scores were highly responsive to change, allowing personalized patient outcomes to be quantified; the qualitative coding framework appears generalizable across different integrative oncology settings and has broader coverage of patient-identified concerns compared with existing cancer-related patient-reported outcome measures.